Analysis of heat gain in computer laboratory and excellent centre by using CLTD/CLF/SCL method - Nina Naisha, Suhaimi; Mohd Yusof, Taib; Ahmad Basirul Subha, Alias; Suziyana, Mat Dahan (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis, Malaysia.